NILAI ISTIMEWA LANSKAP PERDESAAN: LITERATUR REVIEW - Pratiwi, Rian Adetiya; Ikaputra (Program Sarjana Arsitektur Universitas Internasional Batam, 2024)
Landscapes are dynamic and balanced combinations of nature and culture under human influence which form the distinctive character of each region. The cultural landscape formed by the interaction between humans and nature will intentionally produces areas with distinctive characteristics, which cover rural to urban areas. This article aims to find out the forming process of rural landscapes, as well as to identify the special values of rural landscapes. This study was prepared using a literature study approach, by utilizing library sources and documents to obtain research data without going to the field. The rural landscape was originally formed because of basic human needs for life. Rural landscape is land inhabited, cultivated and modified by humans by utilizing its natural resources. Natural landscape patterns are modified in such a way as to create new forms of land use which often present extraordinary characteristics in the form of rural landscapes. The rural landscape is one of the physical manifestations of the cultural landscape, which is the result of human interaction with the natural environment which forms the character of an extensively built landscape which still has stronger natural characteristics than the urban landscape. Rural landscapes have features that include cultural values, social values, economic values, and scientific values and functions. All the processes that occur in the rural landscape will produce a visual product that has a unique aesthetic value.